Negotiating cancer preventative health behaviours and adapting to motherhood: the role of technology in supporting positive health behaviours - Notley, Caitlin; Ward, Emma; Kassianos, Angelos P.; Kurti, Allison; Muirhead, Fiona; Nostikasari, Dian; Payton, Jamie; Spears, Claire Adams (My University, 2020)
Across the UK and USA, postpartum smoking relapse rates are high, and rates of breastfeeding and physical activity are low. This project aimed to explore these interrelated health behaviours and technology use, for intervention development to support postpartum cancer prevention.
Keywords: Cancer prevention; Technological intervention; Motherhood; Identity; Health inequalities